Pengaruh Kegiatan Motorik untuk Meningkatkan Keterampilan Motorik Halus Anak Usia 4 -5 Tahun di PAUD X - Latifa Nur Fajrina; Enoh (UNISBA Press, 2021)
Abstract. Early childhood is a critical period and need to be addressed early on and giving a good stimulus, perfect then all aspects need to be developed. One important aspect of the ability of early childhood development to be developed is of fine motor skills. One of the tasks that must be considered is the activity to cut it, because children develop fine motor skills that can be developed in the future. For it is related to the ability of children to do in group A gem ECD Cendikia Bandung. The purpose of this study to determine the fine motor skills of children before adoption after knowing the fine motor skills of children after the application and after it was seen the effect of fine motor skills as applied to cutting activities. This research method using a quasi-experimental method or One group pretest and posttest design This design is also known as the design of